2014
DOI: 10.1186/s13071-014-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

Absence of genetic structure in Baylisascaris schroederi populations, a giant panda parasite, determined by mitochondrial sequencing

Abstract: BackgroundInfection with the parasitic nematode, Baylisascaris schroederi (Ascaridida: Nematoda), is one of the most important causes of death in giant pandas, and was responsible for half of deaths between 2001 and 2005. Mitochondrial (mt) DNA sequences of parasites can unveil their genetic diversity and depict their likely dynamic evolution and therefore may provide insights into parasite survival and responses to host changes, as well as parasite control.MethodsBased on previous studies, the present study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…Baylisascaris schroederi is a nematode thought to be specific to giant pandas ( Ailuropoda melanoleuca ). Sequence analysis of both ITS and mtDNA have shown a lack of genetic differentiation among B. schroederi from geographically isolated panda populations [ 124 127 ], which is surprising because pandas do not migrate among populations, and pandas from each of these populations are themselves genetically differentiated [ 128 ]. The likely explanation for this difference between host and parasite population genetics is that B. schroederi has a much larger Ne than its host [ 129 ] and so undergoes population differentiation more slowly.…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
See 1 more Smart Citation
“…Baylisascaris schroederi is a nematode thought to be specific to giant pandas ( Ailuropoda melanoleuca ). Sequence analysis of both ITS and mtDNA have shown a lack of genetic differentiation among B. schroederi from geographically isolated panda populations [ 124 127 ], which is surprising because pandas do not migrate among populations, and pandas from each of these populations are themselves genetically differentiated [ 128 ]. The likely explanation for this difference between host and parasite population genetics is that B. schroederi has a much larger Ne than its host [ 129 ] and so undergoes population differentiation more slowly.…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
“…Thus, while there may have been time for panda populations to differentiate through genetic drift in the 200 years since habitat fragmentation began [ 130 ], drift may not have been fast enough to yet differentiate B. schroederi populations. It has also been suggested that B. schroederi gene flow may occur among panda populations in the absence of panda movement, for example through association with a presently unknown paratenic host [ 127 ].…”
Section: Influence Of Anthropogenic Disruption On Parasitic Nematode mentioning
confidence: 99%
“…the Minshan, Qionglai and Qinling mountain ranges). A low level of genetic diversity but a high level of gene flow in worms suggested the potential for a rapid spread of drug resistance in B. schroederi (see Xie et al, 2014). Third, Zhao et al (2014) did not find support for the genetic substructuring within B. schroederi among samples from the Qinling mountains and one sample from Sichuan province using portions of the mitochondrial genes cytb, cox3 and nad5.…”
Section: Geneticsmentioning
confidence: 97%
“…First, Zhou et al (2013a) used the cytb gene and concluded that there was a high rate of gene flow among three populations of B. schroederi representing the two recognised subspecies. Second, Xie et al (2014Xie et al ( , 2015b used portions of the mitochondrial cox1, atp6 and 12S rRNA genes, which displayed very few parsimony informative sites. Again, these authors found no discernable genetic difference in worms among the populations from distinct habitats of the giant panda (i.e.…”
Section: Geneticsmentioning
confidence: 99%
“…schroederi eggs in feces of infected giant pandas. However, after eggs containing L 2 larvae hatch in the host, it takes 77–93 days before they mature and begin to ovulate [ 11 ]. Thus, the currently available methods are unsuitable for early detection of B .…”
Section: Introductionmentioning
confidence: 99%